From General to Contextual: Developing a Subject-Specific Scientific Creativity Test on Simple Machines - Mayaika Mayaika; Suwito Singgih; Riva Ismawati; Galih Albarra Shidiq (Jurnal Pendidikan MIPA, 2026)
This study aimed to develop an instrument for assessing junior high school students’ scientific creativity based on the Scientific Structure Creativity Model (SSCM) in the topic of Work and Simple Machines. The research employed a Research and Development method using the 4D model (Define, Design, Develop, and Disseminate), and was limited to the Develop stage. The research subjects consisted of 100 eighth-grade students from four public junior high schools in Magelang City, selected through purposive sampling, and nine validators (four lecturers and five science teachers) for content validity testing. The define stage included a needs analysis based on the SSCM, a review of the subject matter, and an analysis of learning outcomes. The design stage involved constructing a test blueprint comprising seven essay items and a scoring rubric based on fluency, flexibility, and originality. The develop stage included expert validation, instrument revision, and a limited field trial. The instrument consisted of seven essay questions, adapted from the seven aspects of the SSCM, along with an expert validation sheet assessing content, construct, and language. Content validity was analyzed using Aiken’s V, construct validity was examined through Exploratory Factor Analysis, reliability was measured using McDonald's Omega, and age differences were tested using One-Way ANOVA. The results indicated Aiken’s V values ranging from 0.786 to 0.819, demonstrating good content validity. The KMO value of 0.655 and a significant Bartlett’s Test (p < 0.001) indicated that the data were suitable for factor analysis. McDonald's Omega yielded a value of 0.739, indicating adequate internal consistency. The ANOVA test (p = 0.775) showed no significant difference in scientific creativity scores between students aged 13 and 14 years. The findings indicate that the developed instrument is valid and demonstrates adequate reliability for measuring junior high school students’ scientific creativity in the topic of Work and Simple Machines. Keywords: instrument development, scientific creativity, scientific structure creativity model, work, simple machines.